Digital skills for science-based teaching among Jordanian science teachers: evidence from DiKoLAN framework - Alshorman, Sameera; Aldaraghmeh, Saed Y. (Institute of Advanced Engineering and Science, 2025)
This study examines the digital competencies of Jordanian science teachers using the DiKoLAN framework, assessing seven key domains: presentation (PRE), documentation (DOC), data processing (DAP), communication and collaboration (COM), information search and evaluation (ISE), data acquisition (DAQ), and simulation and modelling (SIM). Employing a mixed-methods design, it integrates survey data from 164 teachers with interview insights from 14 participants. The findings show high proficiency in PRE (M=4.48) and DOC (M=4.28), but lower scores in SIM (M=3.53), reflecting limited integration of advanced tools like artificial intelligence (AI) simulations. Private school teachers reported greater access to resources and training, while public school counterparts faced infrastructural and developmental barriers. The results highlight the need for targeted, subject-specific training and equitable resource allocation to support digital integration in science education. These insights inform policy and curriculum development aimed at bridging digital competency gaps.